Pausing As A Prosodic Correlate Of Speech Units In St’át’imcets (Lillooet Salish) - Caldecott, Marion; Czaykowska-Higgins, Ewa; Fortier, Kyra; Koch, Karsten; Leonard, Janet; Lyon, John (Canadian Acoustics, 2019)
The reliability of pausing as a correlate to prosodic, syntactic and discourse units has been debated in commonly-studied languages.  The question explored in this study is what role (syntactic, prosodic, narrative) does pausing play in one St’át’imcets narrative. Results suggest that pausing is a correlate to discourse and prosodic units rather than syntactic ones.